Investigating sex differences in acute intoxication and verbal memory errors after ad libitum cannabis concentrate use. (1st June 2021) - Gibson, Laurel P.; Gust, Charleen J.; Ellingson, Jarrod M.; YorkWilliams, Sophie L.; Sempio, Cristina; Klawitter, Jost; Bryan, Angela D.; Hutchison, Kent E.; Cinnamon Bidwell, L.
Highlights: The use of high potency cannabis concentrates is increasing in the US. First study to explore sex-differences in the acute effects of concentrates. Participants administered legal market concentrate products ad libitum . Plasma concentrations of THC and CBD were higher in men after acute concentrate use. Men and women reported similar levels of intoxication and impairment. Abstract: Background: An innovative naturalistic at-home administration procedure was used to investigate sex differences in subjective drug effects and verbal memory errors after ad libitum use of high potency state legal market Δ9-tetrahydrocannabinol (THC) concentrate. Methods: Regular concentrate users were randomly assigned to ad libitum administration of one of two cannabis concentrate products (70 % or 90 % THC) that they purchased from a dispensary. 65 participants ( N = 34 men, N = 31 women) were assessed in a mobile pharmacology lab before, immediately after, and 1 -h after ad libitum concentrate use. Plasma cannabinoids (THC, 11-OH-THC, CBD), subjective drug effects, and verbal memory errors were assessed at all three time points. Results: Although men and women exhibited similar plasma 11-OH-THC levels across time ( p = .10), sex differences were found in plasma THC and CBD after legal market concentrate use, with men displaying significantly higher levels of plasma THC and CBD immediately after cannabis concentrate use (plasma THC [ng/mL]: M men = 489.88, M women = 135.08, p < .001; plasma CBD [ng/mL]: M men = 1.14, M women = 0.53, p = .04). Despite this, sex differences in subjective effects and verbal memory errors did not emerge, although women reported a steeper decrease in drug liking after use ( p = .04). Conclusion: These data provide the first look at sex differences after acute naturalistic cannabis concentrate use, and suggest much higher THC exposure in men versus women, but similar acute drug and impairment effects across the sexes. Further studies are needed to determine the mechanisms ( e.g. tolerance, cannabinoid metabolism, smoking topography) behind these findings.